Cytokinins on the Move - Durán-Medina, Yolanda (Front Plant Sci, 2017)
Cytokinins are important signals that participate in different plant processes, and are well known for their strong influence in plant development. With the years, knowledge has been built about their effects, chemical nature, metabolism, and signaling mechanisms. However, one aspect about cytokinins that has been lagging behind is cytokinin transport. Recent reports are providing more information about how cytokinins are transported and how their transport is connected to their effects in development. This review provides a general overview of what is known about cytokinin transport, with a focus on the latest reports.